2013
DOI: 10.1155/2013/563717
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a): A Promising Marker for Residual Cardiovascular Risk Assessment

Abstract: Atherosclerotic cardiovascular diseases (CVD) are still the leading cause of morbidity and mortality worldwide, although optimal medical therapy has been prescribed for primary and secondary preventions. Residual cardiovascular risk for some population groups is still considerably high although target low density lipoprotein-cholesterol (LDL-C) level has been achieved. During the past few decades, compelling pieces of evidence from clinical trials and meta-analyses consistently illustrate that lipoprotein(a) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 109 publications
0
55
0
Order By: Relevance
“…Prognostic value of a significant increase in LP(a) in serum, as an important predictor of CV events, was confirmed in the studies that included patients with dyslipidaemia, hypertension, diabetes, the history of CV disease and non-alcoholic hepatic steatosis (NAHS) [38,72,73]. In parallel, the role of LP(a) as a genetic risk factor for CV disease was explained.…”
Section: Dyslipidaemia and Non-alcoholic Fatty Liver Diseasementioning
confidence: 83%
“…Prognostic value of a significant increase in LP(a) in serum, as an important predictor of CV events, was confirmed in the studies that included patients with dyslipidaemia, hypertension, diabetes, the history of CV disease and non-alcoholic hepatic steatosis (NAHS) [38,72,73]. In parallel, the role of LP(a) as a genetic risk factor for CV disease was explained.…”
Section: Dyslipidaemia and Non-alcoholic Fatty Liver Diseasementioning
confidence: 83%
“…Studies have demonstrated that Lp(a) elevation is associated with impairment of endothelial function and increased risk of cardiovascular events [36,37]. In the long-term follow-up of patients undergoing percutaneous coronary intervention, Kardys et al [38] observed that Lp(a) was associated with a higher 1-year risk of cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers associated positively with prevalent and incident cardiovascular disease including coronary heart disease and stroke include C-reactive protein (hs-CRP) 15 , lipoprotein-associated phospholipase A2 (LpPLA2) 2,6,7 , cardiac troponin T (cTnT) 8 , N-terminal pro-brain natriuretic peptide (NT-proBNP) 9 , lipoprotein(a) (Lp(a)) 1014 , cystatin C 1518 , and urine albumin to creatinine ratio 9,19,20 . Additionally, atherosclerosis as assessed using imaging techniques such as carotid intima media thickness (cIMT), carotid artery plaque, and coronary artery calcium measured on a computed tomography (CT) scan, have also been shown to be associated positively with CVD and to improve coronary heart disease risk prediction 2126 .…”
Section: Introductionmentioning
confidence: 99%